2011
DOI: 10.1614/wt-d-10-00150.1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Tall Waterhemp (Amaranthus tuberculatus) Biotype Resistant to HPPD-Inhibiting Herbicides, Atrazine, and Thifensulfuron in Iowa

Abstract: Seeds of a putative 4-hydroxyphenylpyruvate dioxygenase (HPPD)-inhibiting herbicide–resistant tall waterhemp biotype from Henry County, IA, were collected from a seed corn field in fall 2009 after plants were not controlled following a POST application of mesotrione plus atrazine. The response of this biotype to various herbicide modes of action was evaluated in greenhouse and field tests. Under greenhouse conditions, the suspect biotype showed an eightfold decrease in sensitivity to mesotrione with a 50% cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 15 publications
1
68
0
Order By: Relevance
“…In atrazine-resistant A. retroflexus (possessing an insensitive D1 protein) (Hugie et al, 2008), PRE atrazine followed by POST mesotrione treatments demonstrated a synergistic response, whereas in atrazine-resistant A. theophrasti possessing enhanced GST-mediated metabolism of atrazine, only the POST tank-mix displayed a synergistic response (Woodyard et al, 2009b). However, recent discoveries of mesotrione-and atrazine-resistant waterhemp populations, such as the MCR population from Illinois (Hausman et al, 2011(Hausman et al, , 2016 and a waterhemp population from Iowa (McMullan and Green, 2011), may diminish the ability to achieve POST synergism with HPPD inhibitor-atrazine combinations and, consequently, limit effective POST control options for multiple herbicide-resistant (MHR) waterhemp in maize.…”
Section: Core Ideasmentioning
confidence: 99%
“…In atrazine-resistant A. retroflexus (possessing an insensitive D1 protein) (Hugie et al, 2008), PRE atrazine followed by POST mesotrione treatments demonstrated a synergistic response, whereas in atrazine-resistant A. theophrasti possessing enhanced GST-mediated metabolism of atrazine, only the POST tank-mix displayed a synergistic response (Woodyard et al, 2009b). However, recent discoveries of mesotrione-and atrazine-resistant waterhemp populations, such as the MCR population from Illinois (Hausman et al, 2011(Hausman et al, , 2016 and a waterhemp population from Iowa (McMullan and Green, 2011), may diminish the ability to achieve POST synergism with HPPD inhibitor-atrazine combinations and, consequently, limit effective POST control options for multiple herbicide-resistant (MHR) waterhemp in maize.…”
Section: Core Ideasmentioning
confidence: 99%
“…MCR displayed 10-and 35-fold resistance to mesotrione in comparison with ACR and WCS, respectively, in greenhouse studies (Hausman et al, 2011). In addition, waterhemp populations with similar patterns of multiple resistance have recently been identified (Hausman et al, 2011;McMullan and Green, 2011;Heap, 2012). However, the mechanisms of resistance to mesotrione and atrazine in these waterhemp populations are currently unknown.…”
mentioning
confidence: 99%
“…In addition, just in the last six years it was confirmed that waterhemp biotypes evolved resistance to 4-hydroxyphenylpyruvate dioxygenase (HPPD)-inhibiting herbicides (WSSA SOA Group 27) in Illinois (Hausman et al 2011) and Iowa (McMullan and Green 2011). Therefore, new herbicide options to manage waterhemp are needed .…”
mentioning
confidence: 99%